2011
DOI: 10.1590/s1807-59322011000900017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antidepressants and pilocarpine on rat parotid glands: an immunohistochemical study

Abstract: OBJECTIVES:To evaluate the effects of antidepressants and pilocarpine on the quantity of myoepithelial cells and on the proliferation index of the epithelial cells of rat parotid glands.INTRODUCTION:Hyposalivation, xerostomia, and alterations in saliva composition are important clinical side effects related to the use of antidepressants.METHODS:Ninety male Wistar rats were allocated to nine groups. The control groups received saline for 30 (group C30) or 60 days (group C60) or pilocarpine for 60 days (group Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
3
10
0
6
Order By: Relevance
“…These results were in agreement with those of Mattioli et al [29] who found that pilocarpine used in association with fluoxetine for 60 days did not induce changes in…”
Section: Morphometric and Statistical Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These results were in agreement with those of Mattioli et al [29] who found that pilocarpine used in association with fluoxetine for 60 days did not induce changes in…”
Section: Morphometric and Statistical Resultssupporting
confidence: 93%
“…This finding agreed with the study conducted by Mattioli et al [29], who additionally demonstrated that the use of fluoxetine for 30 days was associated with a decrease in stimulated salivary flow rate, an increase in cellular volume, and an increase in the number of MECs in rats [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Entretanto, alterações dos parâmetros salivares no período gestacional apresentam controvérsias na literatura [8][9][10][11] . Estudos mostram que os antidepressivos têm ação farmacológica sobre o sistema nervoso central, alterando a função das glândulas salivares 12 . As tentativas para esclarecer os efeitos xerostômicos de tais drogas têm sido de grande valor científico, tanto na explicação dos efeitos fisiofarmacológicos quanto em trazer benefícios adicionais para os pacientes que fazem uso destas drogas 12 .…”
Section: Discussionunclassified